Enzymatic cellulose nanocrystal production from pretreated palm oil empty fruits bunch fiber - Sikder, Md. Belal Hossain; Rashid, Shah Samiur; Mohd Hasbi, Ab. Rahim; Aizi Nor Mazila, Ramli; Rasidi, Roslan; Sasi, Ahmed Abdulsalam; Mustafa, Abu Hasnat (Elsevier Ltd, 2022)
Cellulose nanocrystal (CNC) is a biopolymer which has wide application in packaging industries, biomedical fields etc. due to its some desirable characteristics like biodegrade ability, thermal stability etc. CNC is produced from different lignocellulosic biomass by different chemical and physio-co-chemical methods which released more hazardous discharge and not friendly. The enzymatic method can be the alternative and sustainable method for CNC. Palm oil empty fruit bunch (OPEFB) is a major biowaste material from edible oil industries in Malaysia has no measurable value-added process. So, there is looking for environmentally friendly and green process to convert OPEFB to biopolymer like CNC. In this research work, CNC was produced from the extracted cellulose fibre from OPEFB which was delignified by commercial free laccase and hydrolysed using free cellulase as a biocatalyst. Field emission scanning electron microscopy (FESEM) was used to examine the morphology. The yield of CNC reached to 22.53% (w/w) from the enzyme pre-treated 2% (w/v) OPEFB cellulose fibre from 96 hours hydrolysis by 80 International unit (IU) of cellulase. Nano-dimensioned CNC is seen in the morphological study. So, the production of CNC from OPEFB may be value added to the product which support waste to wealth concept. The isolated CNC from pretreated palm oil empty fruits bunch (OPEFB) cellulosic fibre shows a promising characteristic, and the enzymatic hydrolysis is a potential method for CNC production which is environmentally friendly.